2019
DOI: 10.1111/jfpe.13097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size distribution on the in vitro digestion of calcium alginate‐starchy model foods

Abstract: The aim of this study was to investigate through the use of Weibull and Multiscale kinetics models the effect of different particle size distributions on starch hydrolysis during in vitro digestion of calcium alginate filled with gelatinized potato starch as model foods. Three-different model foods (calcium alginate and gelatinized starch with a without alginate beads) were used. Three particle size distributions by applying the amount of 5, 10, and 15 compression cycles were generated and characterized by Ros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The Weibull model This is a four-parameter model that incorporates a shape factor, β, to the three parameters described above for the other models. Possibly at the borders of mono-and bi-phasic digestograms, the model and its variants have been used (Nguyen & Sopade, 2018;Ramıŕez et al, 2019;Barua et al, 2021b;Mahajan et al, 2022) to describe monophasic digestograms:…”
Section: The Logistic Modelmentioning
confidence: 99%
“…The Weibull model This is a four-parameter model that incorporates a shape factor, β, to the three parameters described above for the other models. Possibly at the borders of mono-and bi-phasic digestograms, the model and its variants have been used (Nguyen & Sopade, 2018;Ramıŕez et al, 2019;Barua et al, 2021b;Mahajan et al, 2022) to describe monophasic digestograms:…”
Section: The Logistic Modelmentioning
confidence: 99%
“…producing many sets of parameters with close fittng coefficients). 16 In terms of criterion (i) as mentioned above, a R 2 > 0.99 was selected in the current study depending on a preliminary check with our experimental data, while it is also possible to use a lower R 2 value to better fit experimental data with higher experimental errors. Considering that increasing the number of model parameters almost always improves the goodness of the fit, the criterion (ii) was achieved by applying the 'Akaike information criterion for a small sample size' (AICc) method, with a formula of AICc =n× ln RSS n 21 Here, n is the sample size (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…This step is a prerequisite for a better understanding of the structural basis for the formation of slowly digestible starch and resistant starch in different food systems. 5,16 For example, firstorder kinetics modeling has indicated that the digestion of wheat bread follows the CPS digestion pattern, where the slowly digestible starch fraction consists of relatively intact B-type wheat starch granules. 11 By adjusting the in vitro starch digestibility of wheat porridge, a lower in vivo postprandial glycemia has been achieved, suggesting that the in vitro digestion assay has some implications for human blood glucose levels.…”
Section: Introductionmentioning
confidence: 99%